OPEN EDUCATION IN STUDYING SCIENCES - DEVELOPING OF A EUROPEAN FRAMEWORK - Gabriela Noveanu; Ana-Maria Dalu; Miruna Miulescu; Ciprian Fartușnic (National Academy of Educational Sciences of Ukraine, 2022)
The article presents in detail the main outcomes of a recent action - research project PULCHRA - Science in the city (https://pulchra-schools.eu/), funded by Horizon 2020 EU program, promoted by the University of Athens and a consortium of ten academic and research European institutions, including the Education Research Unit from Romania. The project was inspired by the open education principles (Abrioux, 2009) and creates a complex learning by doing framework for secondary students of 14 to 17 years old. The perspective of City as ecosystem creates for the involved partner schools various opportunities for exploiting inquiry-based methods and addresses real life problems (Pedaste, et al., 2015). After three years of implementation, PULCHRA developed a specific methodology, by promoting real life experiments during science classes, in collaboration with community representatives and the support from partners, experts, and other stakeholders. By using a variety of resources, materials, and teaching approaches, specific science teams managed to research, develop, produce and promote solutions to several common issues/opportunities that European cities face due to increased urbanization. Out of the six environmental, social and economic thematic areas of the project, Romanian schools focused on regenerating urban space to connect people in a healthy environment. The article explores the outcomes at grass-root level, as documented by monitoring and evaluation activities conducted in six upper secondary schools from Romania. In particular, we highlight the contribution of the project in building students' good scientific knowledge, in promoting expert and community participation and encouraging active engagement in shared living environments and futures. The contribution of the project on development of STEM competences, in relation with the national curriculum, is also explored. In the context of COVID pandemics, the article will highlight the importance of the City Challenges Platform, set up to facilitate the learning and collaboration of the members of the city science teams and wider network. The contribution to sharing digital educational material, design relevant experiments and develop distance-learning courses on cities as urban eco-systems will also be documented.